To the 60th anniversary of Professor, grand PhD in technical sciences Vadim Anatolyevich Kovtun - Palevoda, Иван Иванович; Kamlyuk, Андрей Николаевич; Pasovets, Владимир Николаевич; Korotkevich, Сергей Геннадьевич (Journal of Civil Protection, 2023)